Tripled Fixed Point Theorems of Caristi type Contraction in Partially Ordered Metric Space - Adilakshmi, G; N.V.Kishore, G; Veerraju, N (International Journal of Engineering and Technology, 2018)
The main aim of this paper is to obtain a unique common tripled fixed point theorem in partial ordered metric space using Caristi type contraction.Â Â